Advances in Interdisciplinary Engineering Select Proceedings of FLAME 2018 - Kumar, Mukul; Pandey, R. K.; Kumar, Vikas (Lecture Notes in Mechanical Engineering,, 2019)
This book presents select proceedings of the International Conference on Future Learning Aspects of Mechanical Engineering (FLAME 2018). The book discusses interdisciplinary areas such as automobile engineering, mechatronics, applied and structural mechanics, bio-mechanics, biomedical instrumentation, ergonomics, biodynamic modeling, nuclear engineering, agriculture engineering, and farm machineries. The contents of the book will benefit both researchers and professionals. .